Youth farmers’ willingness to Pay for agricultural extension service in Oyo State (2013)
Digital agriculture technologies have the potential to increase the efficiencies and productivity of farmers. However, the use of these digital technologies requires its users to have some level of digital skills – digital literacy. This study, therefore examined the level of digital literacy of crop farmers in Oyo state. A multistage sampling procedure was used in selecting 120 respondents from the study area. A structured questionnaire was used to collect primary data. Data were analysed using descriptive (frequency, percentage, and mean) and inferential statistics (Chi-square and PPMC) were used. Results reveal that majority of the respondents were male (70%), married (90.8%), had no formal education (42.5%), with a mean age of 56 years and average farming experience of 25 years. About 79.0% had between 0.5 and 8 acres of farmland, 68.3% did not practice mixed farming, 73.3%had never used social media, and 72.5% used feature phones. Furthermore, 57.5% had a favourable perception of the use of digital tools with low knowledge (55%) of basic concepts and processes of digital agriculture and platforms. The level of digital literacy (71.7%) among crop farmers in Oyo state was low. Lack of training to develop digital skills ranked the most severe constraint to digital literacy and usage among respondents. However, the perception of the use of digital tools was favourable. The digital literacy level of crop farmers was generally low. There is a need for government to establish a digital literacy initiative specifically targeted at farmers to develop and improve their digital skills through training.